Dati satellitari di osservazione della Terra, strumenti digitali e città sostenibili - Tapete, Deodato (GEOmedia, 2024)
Earth Observation (EO) is nowadays a primary source of geospatial data to address urban applications. As information layers imported into GIS, EO products are increasingly exploited for cartographic purposes to improve cities representation. The Italian Space Agency (ASI) invests in novel satellite-based applications and digital tools facilitating EO data utilization. Such tools include: thematic exploitation platforms enabling EO data processing by nonexpert users through validated processors; dashboards wherein satellite products are among the input data used during the decision-making process; Digital Twins allowing for what-if scenarios and forecast activities. Recent user-driven developments are presented with regard to urban heat island, coastal applications, conservation of cultural heritage, monitoring and modelling of processes related to terrestrial water cycle.